IMPLEMENTASI KAMPUS BERKELANJUTAN BERWAWASAN LINGKUNGAN DI UIN RADEN INTAN LAMPUNG - Apriyani, Hikma; Muhammad Ilham Jaya Kesuma; Muhammad Al Imron; Ali Murtadho; Baharudin; Ikhsan Mustofa (LP2M IAIN Sultan Amai Gorontalo, 2024)
The purpose of this research is to examine the development of the green campus at UIN Raden Intan Lampung. This is due to the fact that sustainable campus development is very important to support sustainable development and reduce the negative impact it has on the environment. One of the data collection methods used in this qualitative research is interviews with informants involved in the development of the Green Campus. The results show that UIN Raden Intan Lampung has developed a Green Campus strategy through the